Bilingual Comparable Corpora and the Training of Translators - Zanettin, Federico (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis article demonstrates how small bilingual corpora of either general or specialised language can be used to devise a variety of structured and self-centred classroom activities whose aim is to enhance the understanding of the source language text and the ability to produce fluent target language texts.